The ethnographer's way a handbook for multidimensional research design - Peterson, Kristin 1966-; Olson, Valerie (Duke University Press, 2024)
The Ethnographer's Way guides researchers through the exciting process of turning an initial idea into an in-depth research project. Kristin Peterson and Valerie Olson introduce "multidimensioning," a method for planning projects that invites scholars to examine their research interests from all angles. Researchers learn to integrate seemingly disparate groups, processes, sites, and things into a unified conceptual framework. The handbook's ten modules walk readers step-by-step, from the initial lightbulb moment to constructing research descriptions, planning data gathering, writing grant and dissertation proposals, and preparing for fieldwork. Designed for ethnographers and those working across disciplines, these modules provide examples of multidimensional research projects with exercises readers can utilize to formulate their own projects. The authors incorporate group work into each module to break the isolation common in academic project design. In so doing, Peterson and Olson's handbook provides essential support and guidance for researchers working at all levels and stages of a project
Keywords: SOCIAL SCIENCE / Anthropology / Cultural & Social; Anthropology -- Research -- Methodology; Ethnology -- Research -- Methodology; Research -- Methodology; Feldforschung; Forschungsprojekt; Ethnologie; Kulturanthropologie; Forschungsmethode